Combined Porous-Monolithic TiNi Materials Surface-Modified with Electron Beam for New-Generation Rib Endoprostheses; Journal of Functional Biomaterials; Vol. 14, iss. 5 - Shabalina A. V. Anastasiya Valerjevna; Anikeev S. G. Sergey; Kulinich S. A. Sergei; Artyukhova N. V. Nadezhda Viktorovna; Vlasov V. A. Vitaliy Anatolievich; Kaftaranova M. I. Maria Ivanovna; Khodorenko V. N. Valentina Nikolaevna; Yakovlev E. V. Evgeny Vitaljevich; Pesterev E. A. Evgeny Aleksandrovich; Lukyanenko A. V. Anna Vitaljevna; Volochaev M. N. Mikhail Nikolaevich; Pakholkina S. A. Sofiya Aleksandrovna; et al. (2023, 2023)
Title screen